Transformation of Product Marketing Strategies in Enhancing Trade Competitiveness in the Global Market - Nora Maulana; Rita Mulyani; Dicky Armanda; Safwan Safwan; Muhamad Tarmizi Bin Shamshul Arif (Syarah: Jurnal Hukum Islam dan Ekonomi, 2025)
Marketing strategy transformation plays a vital role for business actors, especially those affiliated with State-Owned Enterprises in North Aceh and Lhokseumawe City, in their efforts to increase the competitiveness of domestic products in the global market. This research is classified as field research adopting a descriptive qualitative approach. Research data was obtained through observation, interviews, focus group discussions, and documentation. Qualitative data analysis was conducted continuously until the collected data reached saturation point. The steps in data analysis began with data reduction, data presentation, conclusion drawing, and data verification. The findings of the study indicate that marketing strategy transformation is very important for business actors at State-Owned Enterprises in North Aceh and Lhokseumawe City to increase the competitiveness of domestic products in the global market. Despite producing high-quality products, business actors face challenges such as weak branding, limited distribution, intense competition, and a lack of understanding of the global market. Limited capital and infrastructure also pose obstacles. To compete, business actors need to adopt marketing strategies based on in-depth market research, improve product quality, and enhance their understanding of global market dynamics.